Utilising Fiscal Instruments to Drive Economic Growth Effectively - Lutsyk Anatolii; Pravdiuk Maryna; Deneha Oleh; Puhalskyi Vadym; Shepel Inesa (Salud, Ciencia y Tecnología – Serie de Conferencias. 2025; 4., 2025)
Introduction: in these times of contemporary crises, fiscal policy has a key role to play in the national resilience and economic stability. These challenges have become even more pressing due to Ukraine’s ongoing war and need substantial financial means to recover. Method: this study is a review of the effect tax revenues to budget income. It is grounded on literature sources and statistic data with more than thirty bibliographic references of academic papers, official reports and policy documents. Results: the research emphasizes that during conflict there is the necessity to optimize existing financial resources as well as look for additional sources of revenue. This reinforces how such fiscal policies play to cultivate economic growth, stabilize finances and appropriately utilize the instruments of taxation. This shows trends of nation revenues and expenditures and acknowledge to the fact that taxation is one of the means of be-fitting financial demand as well as maintaining the economy stable. Conclusions: fiscal reserves and tax instruments are needed under martial law for maintaining financial stability. But for the effective implementation of these the administrative structures need to be enhanced. Especially during the crisis, we need a balanced tax burden, a favourable business climate and new revenue sources.